Torg ratios based on cervical lateral plain films in normal subjects - Tjahjadi, David; Onibala, MZ (Universa Medicina, 2010)
Stenosis of the spinal canal can be caused by trauma, degenerative processes, and tumors, causing a neurological deficit. If the neurological deficit could be detected or diagnosed earlier, the late complications such as quadriparesis could be prevented. The Torg ratio can be used to find evidence of cervical canal stenosis on lateral plain film, as it has the advantage of not being affected by magnification. The purpose of this study was to determine the Torg ratio for normal subjects using lateral plain films of cervical vertebrae. This cross-sectional study was done at the Department of Radiology FKUI/RSUPN-CM Jakarta, starting from September 16 – 20, 2008. The study included 98 subjects, aged 20 – 40 years, were the mean age of the subjects was 27.4 years (SD ± 5.4). All participants were subjected to measurement of the Torg ratio by cervical lateral plain film. The mean Torg ratio of normal subjects was 0.99 for males and 1.06 for females. The mean Torg ratio of several ethnicities were 1.04 for Javanese, 1.02 for Sundanese, 1.01 for Betawi, and 0.99 for other ethnicities. The mean Torg ratio of our subjects is different from that of other people, such as Pakistanis, Singaporeans, and Koreans. The mean Torg ratios of ethnicities are not significantly different from one another. Therefore, the Torg ratio can be relied upon to predict narrowing of the cervical spinal canal in the sagittal plane.